Adaptations in Maternofetal Calcium Transport in Relation to Placental Size and Fetal Sex in Mice - Hayward, Christina E.; Renshall, Lewis J.; Sibley, Colin P.; Greenwood, Susan L.; Dilworth, Mark R. (Frontiers in Physiology, 2017)
Appropriate placental transport of calcium is essential for normal fetal skeletal mineralisation. In fetal growth restriction (FGR), the failure of a fetus to achieve its growth potential, a number of placental nutrient transport systems show reduced activity but, in the case of calcium, placental transport is increased. In a genetic mouse model of FGR this increase, or adaptation, maintains appropriate fetal calcium content, relative to the size of the fetus, despite a small, dysfunctional placenta. It is unknown whether such an adaptation is also apparent in small, but normally functioning placentas. We tested the hypothesis that calcium transfer would be up-regulated in the lightest versus heaviest placentas in the same C57Bl/6J wild-type (WT) mouse litter. Since lightest placentas are often from females, we also assessed whether fetal sex influenced placental calcium transfer. Placentas and fetuses were collected at embryonic day (E)16.5 and 18.5; the lightest and heaviest placentas, and female and male fetuses, were identified. Unidirectional maternofetal calcium clearance (CaKmf) was assessed following 45Ca administration to the dam and subsequent radiolabel counts within the fetuses. Placental expression of calcium pathway components was measured by Western blot. Data (median) are lightest placenta expressed as percentage of the heaviest within a litter and analysed by Wilcoxon signed-rank test. In WT mice having normally grown fetuses, CaKmf, per gram placenta near term, in the lightest placentas was increased (126%; P<0.05) in association with reduced fetal calcium accretion earlier in gestation (92%; P<0.05), that was subsequently normalised near term. Increased placental expression of calbindin-D9K, an important calcium binding protein, was observed in the lightest placentas near term (122%; P<0.01). There was no difference in fetal calcium accretion between male and female littermates but a trend towards higher CaKmf in females (P=0.055). These data suggest a small, normal placenta adapts calcium transfer according to its size, as previously demonstrated in a mouse model of FGR. Fetal sex had limited influence on this adaptive increase. These adaptations are potentially driven by fetal nutrient demand, as evidenced by the normalisation of fetal calcium content. Understanding the regulatory mechanisms involved may provide novel avenues for treating placental dysfunction.